TRANSITIONING MATHEMATICS INSTRUCTION TO XITSONGA HOME LANGUAGE IN GRADE 4 CLASSROOMS: A SOCIOCULTURAL PERSPECTIVE - Hlayisani Hlungwane; Hlaviso Motlhaka (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
In South Africa, the Language in Education Policy encourages the use of learners’ home languages in the foundation phase while also promoting multilingualism. However, many learners experience a transition in Grade 4 where the language of learning and teaching changes, often from an African home language to English. This shift has significant implications for mathematics learning because mathematical understanding depends heavily on communication, reasoning, interpretation of concepts, and classroom interaction. This qualitative study examined the policy mandating Xitsonga as the LoLT for Grade 4 Mathematics in Limpopo Province. The study was grounded in sociocultural theory and ubuntu principles. The sample comprised two Grade 4 Mathematics and ten Grade 4 learners. Data were collected through semi-structured teacher interviews and textual analysis of Grade 4 Mathematics examination papers. The findings suggest that transitioning mathematics instruction to Xitsonga in Grade 4 classrooms supports meaningful learning, participation, and conceptual understanding when viewed through a sociocultural lens. The study has implications for learners, Department of Basic Education and future research. For learners, this supports confidence, critical thinking, and collaborative learning, which are central principles of sociocultural learning theory. For teachers, the Department of Basic Education may need to invest in teacher training, translation of mathematics resources, and monitoring of multilingual education practices to ensure successful implementation. Future research, more research is needed on the development of mathematics terminology and teaching materials in African languages to strengthen the implementation of multilingual education policies in South Africa.